Pengaruh Lingkungan Fisik, Lingkungan Non Fisik, Dan Keterampilan Terhadap Produktivitas Kerja Karyawan Pada Pt. Pjb Up Brantas Karangkates Kab. Malang - Muliana Nafiah; Abdul Kodir Djaelani; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThe purpose of this study was to determine the Effect of Physical Environment, Non-Physical Environment, and Skills on Employee Work Productivity at PT. Acting UP Brantas Karangkates. The population in this study were all employees at PT. PJB UP Brantas Malang in 2020, amounting to 107. Samples were taken by proportional random sampling technique Samples and obtained 84 employees based on criteria. This research uses multiple linear regression models. The results of this study indicate that the Physical Environment, Non-Physical Environment, and Skill affect Employee Productivity. Physical environment has a positive effect on employee work productivity, non-physical environment has a positive effect on employee work productivity, and skills have a positive effect on employee work productivity.Keywords: Physical Environment, Non-Physical Environment, Work Skills, and Employee Productivity.